Why so many women still take their husband’s last name - Duncan, Simon (The Conversation, 2020)
While some women may be actively involved in choosing their marital name, taking the man’s name remains the norm.
Keywords: 2000 à aujourd'hui; 2010-2019; angleterre; approches et analyses; cours; discipline; droit des femmes*; famille; histoire et politique; mariage; norvège; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques

Femmes noires francophones: une réflexion sur le patriarcat et le racisme aux XXe-XXIe siècles - Angone, Odome (Collection Kala éditions, 2020)
"Sous l'égide symbolique du soixantenaire des Indépendances Africaines, Femmes Noires Contemporaines livre une réflexion subsaharienne sur le patriarcat et le sexisme aux XXe-XXIe siècles. L'ouvrage, fort de nombreux témoignages récents de femmes, est nourri par des questionnements, des enjeux et des interpellations collectives liées à une époque où, sans plus déléguer leur parole à des intermédiaires ou des médiateurs, les femmes ont désormais leur mot à dire sur des questions qui les concernent directement. Parler de LA femme noire et africaine, c'est révéler l'histoire de ces innombrables vies contraintes et de ces voix réduites au silence, de ces ferveurs et ces rêves étouffés, de ces existences confinées, délimitées par des frontières imposées. L'auteure dresse ici le portrait de cette femme, reléguée dans un ghetto hors du temps, à qui le racisme et le patriarcat contestent le droit à la parole, à qui on dénie le droit élémentaire et légitime de parler en son nom propre."
Keywords: OFDIG; afrique; afro-féminisme; approches et analyses; discipline; femmes* noires; féminisme africain; féminisme décolonial; féminismes noirs; histoire et politique; mouvements sociaux; patriarcat; racisme; régions géographiques; sciences humaines; sciences sociales; sexisme; systèmes d'oppressions; thématiques

Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (ideas series, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics--one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie